2022
DOI: 10.3390/vaccines10081193
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Breakthrough Infections: Incidence and Risk Factors in a Large European Multicentric Cohort of Health Workers

Abstract: Background: The research aimed to investigate the incidence of SARS-CoV-2 breakthrough infections and their determinants in a large European cohort of more than 60,000 health workers. Methods: A multicentric retrospective cohort study, involving 12 European centers, was carried out within the ORCHESTRA project, collecting data up to 18 November 2021 on fully vaccinated health workers. The cumulative incidence of SARS-CoV-2 breakthrough infections was investigated with its association with occupational and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 39 publications
(45 reference statements)
1
24
0
1
Order By: Relevance
“… 31 A multicentric retrospective cohort study in HCWs found that higher antibody titres were associated with decreased risk of SARS-CoV-2 breakthrough infections. 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 A multicentric retrospective cohort study in HCWs found that higher antibody titres were associated with decreased risk of SARS-CoV-2 breakthrough infections. 32 …”
Section: Discussionmentioning
confidence: 99%
“…These include direct viral invasion via ACE2 receptors, hidden viral reservoirs, immune and inflammatory disturbances, altered microbiome, imbalance in the renin-angiotensin system, and abnormal metabolism and mitochondrial dysfunction. 32 Which of these particular mechanisms is responsible for the development of the specific sequelae remains to be explored. Abnormal immunometabolism and mitochondrial dysfunction could be responsible for fatigue 33 while residual reservoir of the virus may lead to loss of smell and taste.…”
Section: Discussionmentioning
confidence: 99%
“…Other literature studies have also shown a lower incidence of BIs. In a recent large European multi-center study on a cohort of HCWs, the cumulative incidence of BIs from February 2021 to November 2021 was 1.2% [ 28 ]. In the study by Raju Vaishya et al, 85 of 3235 (2.63%) vaccinated HCWs contracted the SARS-CoV-2 infection after vaccination in a study period from 16 January to 24 April 2021 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated during the pandemic concerning epidemic intelligence promotion, internal processes reorientation, COVID-19 case management, and specific training and continuous education (e.g., contact tracing and the correct use of personal protective equipment) [ 25 ]. On the subject of risk assessment and nosocomial risk management, it was necessary to implement immediate anti-contagion protocols to safely contain the pandemic to ensure the protection of patients and hospital staff [ 26 , 27 , 28 ], and to continue promoting safe behavior; also, in order to fight breakthrough infections [ 29 ]. Furthermore, with reference to territorial control activities, numerous HCWs provided support to schools [ 30 ], businesses, private companies, and associations following prevention protocols, as well as interservice inspections to jointly assess the risks at the local level [ 31 ].…”
Section: Discussionmentioning
confidence: 99%